Stress responses of Eisenia andrei and Enchytraeus doerjesi (Oligochaeta) to combined effects of temperature and metal contamination - Otomo, Patricks Voua (Stellenbosch : Stellenbosch University, 2011)
Thesis (PhD)--Stellenbosch University, 2011.